Storm water treatment using bio-ecological drainage system - Ayub K.R.; Sidek L.M.; Ainan A.; Zakaria N.A.; Ghani A.A.; Rozi A. (2023)
The treatment of stormwater as it flows through a Bio-Ecological Drainage System (BIOECODS) is the result of a complex interaction between the physical, chemical and biological processes that occur within the system. A stormwater quality monitoring programme at BIOECODS is being carried out by grab sampling method for the period of April-November 2003. Samples of stormwater are taken from ten stations along ecological swales and eight stations along ecological pond. The ecological pond (wet pond, detention pond, constructed wetland, wading river and recreational pond) which is placed downstream acting as a facility to control the storm water quantity and storm water treatment device before storm water flows into Kerian River. The ecological pond system is strategically placed at the downstream end of the BIOECODS to optimize and effectively attenuate and treat storm water runoff generated from the USM Engineering Campus development area. 2005 Taylor and Francis Group, LLC.